2014
DOI: 10.1051/0004-6361/201323225
|View full text |Cite
|
Sign up to set email alerts
|

Fast magnetohydrodynamic oscillation of longitudinally inhomogeneous prominence threads: an analogue with quantum harmonic oscillator

Abstract: Context. Previous works indicate that the frequency ratio of second and first harmonics of kink oscillations tends towards 3 in the case of prominence threads. This is not a straightforward result, so it requires adequate explanation. Aims. We aim to study the magnetohydrodynamic oscillations of longitudinally inhomogeneous prominence threads and to shed light on the problem of the frequency ratio. Methods. The classical Sturm-Liouville problem is used for the threads with longitudinally inhomogeneous plasma d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…The results computed in the present paper for a thread with a parabolic density profile are in disagreement with those obtained by Lomineishvili et al (2014) using the same model. Lomineishvili et al (2014) claim that the period ratio is 3, but we found that the correct value of the period ratio is 2.22, approximately. Here we explain the source of the discrepancy between the results of Lomineishvili et al (2014) and those of the present paper.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The results computed in the present paper for a thread with a parabolic density profile are in disagreement with those obtained by Lomineishvili et al (2014) using the same model. Lomineishvili et al (2014) claim that the period ratio is 3, but we found that the correct value of the period ratio is 2.22, approximately. Here we explain the source of the discrepancy between the results of Lomineishvili et al (2014) and those of the present paper.…”
Section: Discussioncontrasting
confidence: 88%
“…Lomineishvili et al (2014) claim that the period ratio is 3, but we found that the correct value of the period ratio is 2.22, approximately. Here we explain the source of the discrepancy between the results of Lomineishvili et al (2014) and those of the present paper.…”
Section: Appendix A: Comment On the Paper By Lomineishvili Et Al (2014)mentioning
confidence: 65%
See 1 more Smart Citation
“…Pascoe et al 2009a). Lomineishvili et al (2014) also discuss a kink mode period ratio greater than unity for prominence threads, which are denser at the apex than the footpoints.…”
Section: Discussionmentioning
confidence: 98%
“…The ratio being greater than unity suggests a negative scale height, also considered by Andries et al (2005) for coronal loops and Lomineishvili et al (2014) for prominence threads.…”
Section: Introductionmentioning
confidence: 96%